New Horizons : reconnaissance of the Pluto-Charon System and the Kuiper Belt - Russell, C. T. (Christopher T.) (Springer, 2017)
This collection of articles describes the New Horizons mission, its spacecraft, instruments and scientific investigations. It begins with a historical overview of the events leading to the New Horizons mission by the Principal Investigator, Alan Stern. This introduction to the mission is followed by a description of the spacecraft by G.H. Fountain and colleagues. A critical aspect of the mission is the Jupiter gravity assist that was essential in speed- ing the spacecraft on its way to the Pluto–Charon system. The mission design that enabled the gravity assist and the observations to be obtained at Pluto and Charon is described by Y. Guo and R.W. Farquhar. Next H. Weaver and colleagues describe the science payload and L.A. Young and colleagues describe the anticipated scientific investigations. The volume closes with seven articles describing the instruments and investigations. D.C. Reuter et al. discuss Ralph; the visible and infrared imager. S.A. Stern et al. describe the UV imaging spectrograph. A.F. Cheng et al cover the long-range reconnaissance imager, LORRI. G.L. Tyler et al., present the radio science experiment, REX. D.J. McComas et al. describes the solar wind instrument. R.L. McNutt et al. discusses the energetic particle spectrometer science investigation, PEPSSI. Finally M. Horanyi and colleagues describe the Student Dust Counter